Analisis Faktor-Faktor Yang Memengaruhi Minat Siswa Pada Kegiatan Student Day Tata Rias Pasca Pandemi Covid-19 - Nur Safitri Rahmalina (Journal of Student Research, 2023)
The background of this research is due to the phenomenon of students' lack of interest in participating in cosmetology student day activities after the COVID-19. This can be seen from the lack of enthusiasm of students during the learning process. This study aims to identify and describe the factors that influence students' interest in student day cosmetology activities after the COVID-19. This type of research is descriptive quantitative using survey methods. The population of this study was 25 students of class XI who participated in cosmetology student day activities. The sample selection used a census/total sampling technique where all members of the population were used as research samples. Data collection techniques using observation, interviews and questionnaires with the Likert Scale model. The results showed that students' interest in cosmetology student day activities after the COVID-19 was in the moderate category, which was 48%. The indicator with the highest percentage influencing students' interest in student day cosmetology activities after the COVID-19, namely the motivational indicator included in internal factors was in the moderate category at 60%. Meanwhile, school environment indicators which are included in external factors in influencing students' interest in participating in cosmetology student day activities after the COVID-19 pandemic are in the moderate category at 52%